Lipid profile in non-insulin dependent diabetes mellitus with microalbuminuria - I Gde Raka Widiana I Gde Raka Widiana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
To detennine whether non-insulin dependent diabetes mellitus (NIDDM) patients with microalbuminuria have significant abnormality in lipid profile which could result in increasing the cardiovascular risk, a cross sectional study had been conducted by matching in-patient and out-patient of the Department of Medicine, Dr. Sardjito General Hospital, Yogyakarta between October 1990 to May 1992.NIDDM patients with urinary albumin excretion rates (UAER) of 30 to 300 mg per 24 hours (microalbuminuria, incipient nephropathy) were matched for age and sex with NIDDM patients with UAER below 30 mg per 24 hours (control group). Venous blood samples were taken to determine blood sugar, total cholesterol, high density lipoprotein (HDL) cholesterol, low density lipoprotein (LDL) cholesterol and triglyceride levels. Sex. age. duration of diabetes, relative body weight, retinopathy and neuropathy were also determined.Four groups of 34 NIDDM with microalbuminuria (17 males and 17 females) were found, and 34 controls (17 males and 17 females) were studied. There were no significant difference in age, duration of diabetes, relative body weight and neuropathy. However, retinopathy was significantly higher in diabetic patient with microalbuminuria. No significant difference was found in LDL-cholesterol (122,58 ± 59,09 mg/di vs. 113,55 ± 42,25 mg/di, p = 0,24) and triglyceride (173.91 ± 89.06 mg/dl vs. 164.69 ± 69.69 mg/di, p = 0.31), fasting blood sugar (202.55 ± 87.01 mg/dl vs. 23061 ± 111.93 mg/dl, p = 0.13) and 2 hours after meal (253.91 + 89.46 mg/di vs. 284.38 + 114.40 mg/di, p = 0.11) in both groups. However HDL-cholesterol levels (35.94 ± 13.65 mg/dl vs. 4.3 ± 12.32 mg/di, p = 0.01) was significantly lower and the ratio of total cholesteroVHDL-cholesterol (6.31 ± 3.08 vs. 4.1 ± 1.13, p = 0.00017) was significantly higher in NIDDM patients with microalbuminuria compared to the control group...Key Words: diabetes mellitus - lipid profile - cholesterol - HDL cholesterol - cardiovascular risk factors